Dairy cow management and welfare: practices on dairy operations in the United States that may impact dairy cow welfare, lameness, and beef quality assurance - Adams, Ashley E., author; Román-Muñiz, Ivette N., advisor; Olea-Popelka, Francisco J., committee member; Lombard, Jaosn E., committee member; Ahola, Jason K., committee member; Edwards-Callaway, Lily, committee member (Colorado State University. Libraries, 2015)
To view the abstract, please see the full text of the document.
Keywords: dairy cow; welfare; lameness; beef quality assurance